The blue book : a must-see, can't-miss, won't-forget guide to Nantucket - Hilderbrand, Elin (Little Brown and Company, 2025)
"Half the fun of an Elin Hilderbrand Nantucket novel is her attention to local detail: the beaches, restaurants, shops, and scenic destinations are as memorable as her plots and characters. For years Elin's fans have made pilgrimages to the places they know from her books, and for years they've asked for a single guidebook to "Elin's Nantucket." The wait is over: in The Blue Book, the Queen of the Beach Read - and dare we say the Queen of Nantucket - offers readers practical, fun, insider tips: from drive-on beaches to late-night dance bars; from romantic getaways to family outings; from where to find the best oysters to where to buy the best beach towel. Interspersed with scenes from Elin's novels set at the locations she recommends, with charming watercolor illustrations throughout, The Blue Book lets readers plan the perfect getaway - and live like the characters in an Elin Hilderbrand novel." -- Amazon.